Reduction of Cadmium Uptake of Rice Plants Using Soil Amendments in High Cadmium Contaminated Soil: A Pot Experiment - Dian Siswanto; Parinda Suksabye; Paitip Thiravetyan (Journal of Tropical Life Science, 2013)
The aims of this study were to investigate the effect of agricultural residues on reducing cadmium uptake in rice plants. The rice plants growing on no cadmium/free cadmium soils (N), Cd soils (Cds), and Cd soils each amended with 1% w/w of coir pith (CP), coir pith modified with sodium hydroxide (CPm) and corncob (CC) under high cadmium contaminated soil with an average 145 mg Cd kg-1 soil were investigated. The results showed that the cumulative transpiration of rice grown in various treatments under high cadmium contaminated soil followed the order: Cds > CPm â‰¥ CP â‰¥ CC. These transpirations directly influenced cadmium accumulation in shoots and husks of rice plants. The CC and CP seemed to work to reduce the cadmium uptake by rice plants indicated by accumulated cadmium in the husk that were 2.47 and 7.38 mg Cd kg-1 dry weight, respectively. Overall, transpiration tended to drive cadmium accumulation in plants for rice grown in high cadmium contaminated soil. The more that plants uptake cadmium, the lower cadmium that remains in the soil. Keywords: Transpiration, Cadmium Uptake, Rice plant, Agricultural Residues